Pendamping Travelling: Kajian Antropologi Sosial tentang Mahram - Maimun, Muhammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
This anthropologi.cal study of mahram aims to analyze why a culture prohibits marriage between siblings and marriage between a parent and a child. The term is recognized as incest marriage or in Islam those relationships constitute mahram. In Islam as exemplified in the Qur'an and had.its, mahram is not only about forbidden marriage system, but also about something else, like women's travelling. Theoretically, incest might menace human life bio